2020
DOI: 10.3390/app10093310
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of AISI 316L Produced by Directed Energy Deposition-Based Additive Manufacturing: A Review

Abstract: Directed energy deposition (DED) as a metal additive manufacturing technology can be used to produce or repair complex shape parts in a layer-wise process using powder or wire. Thanks to its advantages in the fabrication of net-shape and functionally graded components, DED could attract significant interest in the production of high-value parts for different engineering applications. Nevertheless, the industrialization of this technology remains challenging, mainly because of the lack of knowledge regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 85 publications
0
58
0
12
Order By: Relevance
“…Microstructural tuning in order to tailor mechanical properties has great importance. It is evident from the extensive literature in metal AM [4][5][6][7][8][9][10][11][12][13][14]. Studies on grain morphology, melt pool solidification, solidification texture, the temperature gradient in the melt pool, the affect of cooling rate on morphology, and size of the microstructure are reported for AM [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Microstructural tuning in order to tailor mechanical properties has great importance. It is evident from the extensive literature in metal AM [4][5][6][7][8][9][10][11][12][13][14]. Studies on grain morphology, melt pool solidification, solidification texture, the temperature gradient in the melt pool, the affect of cooling rate on morphology, and size of the microstructure are reported for AM [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Table 3, in fact, the LP parameters cause the solidification of finer Îł cells. As suggested in previous work, the high Yield Strength (YS) and Ultimate Tensile Strength (UTS) of AM 316L is mainly related to the fine cell size and dislocation densities [36,37]. Tensile properties of 316L samples produced by LP-DED using LP parameters and a powder provided by a different producer are also reported [7].…”
Section: Resultsmentioning
confidence: 72%
“…The z-oriented tensile bars fulfilled the yield strength requirement for all tested process settings but failed to comply with the ultimate tensile strength and elongation requirements. Anisotropic mechanical properties in additively manufactured components are a common occurrence and are known to originate in the microstructure [17,22,23]. Thermal treatment throughout the entire build cycle due to elevated build temperatures in the EBMbuild chamber have a history of producing as-built materials with good strength, high ductility, and low residual stress [24], which explains the high elongation at break recorded for the xy-oriented tensile bars.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 316L is a desirable choice for industrial adaptation for EBM. Using 316L(N) for additive manufacturing is not novel in itself; laser-PBF [12][13][14] and directed energy deposition [15][16][17] methods have been used to process 316L feedstock into solid parts. The novelty is found with the adaptation of the EBM process to the 316LN powder feedstock, and where previously mentioned research has demonstrated the feasibility of using EBM for 316LN for producing parts, this work explores the processing parameter space for which good, solid parts can be manufactured.…”
Section: Introductionmentioning
confidence: 99%